SHARĪʿAH PERSPECTIVES ON INTELLECTUAL PROPERTY: ASSESSING THE PERMISSIBILITY OF INTANGIBLE ASSETS IN ISLAMIC COMMERCE - Torres Fernández, Antonio (An-Nahdlah: Journal of Islamic Studies, 2024)
This paper delves into the intricate interplay between Islamic jurisprudence and contemporary trade dynamics, particularly focusing on the legitimacy of ideas as subjects of Islamic commerce. Acknowledging the historical foundation of commercial transactions and their evolution in tandem with scientific and technological progress, this scholarly exploration navigates the expanding landscape of trade, now encompassing intangible assets such as intellectual and industrial property. Within established legal frameworks, the transfer of trademarks and patents generates tangible economic returns. However, this study posits a pivotal inquiry within the context of Islamic jurisprudence: To what extent can ideas legitimately serve as subjects of Islamic commerce? Grounded in Shariah principles, this research endeavors to elucidate the permissibility of positioning ideas as viable entities within Islamic commercial practices. Through an in-depth examination, this scholarly exploration aims to unravel the complex relationship between theological doctrines and commercial imperatives. By probing the boundaries and ethical considerations inherent in trading intangible assets, this study seeks to contribute to a nuanced understanding of how Islamic principles intersect with the evolving landscape of commerce, particularly concerning the legitimacy of ideas within this framework.